Pemanfaatan Media Infografis Dalam Pembelajaran Sejarah di SMA Al-Khairiyah Samarinda - Muhammad Azhari; Wingkolatin Wingkolatin; Muhammad Azmi (Amarthapura: Historical Studies Journal, 2022)
This study aims to determine the use of infographic media in learning history at SMA Al-Khairiyah Samarinda. The discussion in this study will focus on two things. First, to find out how to use infographic media in learning history at SMA Al-Khairiyah Samarinda. Second, to find out what are the obstacles to using infographic media in history learning at Al-Khairiyah High School Samarinda. The method used in this study is a qualitative approach with a descriptive method. Data collection is done by interview, observation and documentation. The results of the study show that the first finding is that educators easily convey learning materials and most students easily understand history lessons. While the results of the second study indicate that the obstacles faced by educators are the lack of facilities and infrastructure in schools and the limited time in preparing the material. The use of infographic media in learning history at SMA Al-Khairiyah Samarinda provides convenience in teaching and learning activities for both teachers and students.